Impact of amino acid supplementation on hydroponic lettuce (Lactuca sativa L.) growth and nutrient content - Shumaila Khan; Muhammad Zafar Iqbal; Farheen Solangi; Shahid Azeem; Muhammad Adnan Bodlah; Muhammad Saqlain Zaheer; Yasir Niaz; Muhammad Ashraf; Muhammad Abid; Hera Gul; Hongjun Yu; Qiang Li; et al. (Scientific Reports)
Abstract Lettuce (Lactuca sativa L.), a widely cultivated leafy green, is valued for its rich content of bioactive compounds, including folates, vitamins, tocopherols, ascorbic acid, and antioxidants. This study aimed to evaluate the effects of amino acid supplementation on the growth and nutrient content of hydroponically grown lettuce. A greenhouse experiment using a completely randomized design (CRD) was conducted, with three replications and three plants per replication. There were 4 treatments (T0 (Control), T1 (Methionine 20 mg/L), T2 (Tryptophan 220 mg/L, T3 (Glycine 200 mg/L) of this experiment Growth parameters, including biomass, leaf length, leaf width, and leaf area, were measured four weeks after transplantation. L-methionine supplementation resulted in a significant improvement in plant growth, with a 23.60% increase in biomass and a 31.41% increase in leaf area. Conversely, L-tryptophan treatment led to substantial reductions in growth, including a 98.78% decrease in biomass. Nutrient analysis revealed that amino acid treatments, especially methionine, enhanced the nitrogen, phosphorus, and potassium content in leaf tissues. These results suggest that L-methionine has a positive effect on both growth and nutrient uptake in hydroponic lettuce, while L-tryptophan and L-glycine negatively affect plant development. The differential responses to amino acid treatments may be attributed to their distinct roles in plant metabolism, with methionine enhancing sulfur-containing compounds and proteins essential for growth, while tryptophan and glycine could disrupt metabolic pathways. Future research should explore the mechanisms underlying these effects and evaluate the optimal amino acid concentrations for maximizing hydroponic lettuce production and nutrient density.